Distribuição geográfica e conservação de Callicebus coimbrai Kobayashi & Langguth, 1999 (Primates – Pithaeciidae) na Mata Atlântica do nordeste do Brasil. - Jerusalinsky, Leandro (2013)
The Coimbra-Filho titi monkey, Callicebus coimbrai, was the last primate described in the Atlantic Forest, inhabiting Sergipe and the northern coast of Bahia. The limits of geographic distribution, especially in the west, were not well known, making it difficult to estimate the extent of occurrence of the species and to guide management strategies. The region occupied by C. coimbrai has had successive economic cycles since the 16th century, resulting in severe habitat loss and fragmentation. Thus, C. coimbrai was considered at risk of extinction immediately after its discovery, but there were no detailed estimates of remaining populations, extent of the area occupied by the species, characterization of threats, ecological requirements or population viability. The general objective of the present work was to investigate the geographic distribution and the conservation status of C. coimbrai, aiming to support management strategies for the conservation of the species. The specific objectives were: 1) to identify the remaining populations of C. coimbrai and the ecological and geographic factors that determine their presence or absence, and distribution limits in relation to C. barbarabrownae; 2) to analyze the potential distribution of C. coimbrai and its biogeographic relationships with the other species of the Personatus group, with emphasis on the limits with C. barbarabrownae; 3) to diagnose the conservation status of C. coimbrai populations, estimating their extent of occurrence, occupation area and remaining population, and characterizing the main threats to their populations; and 4) to evaluate the population viability of C. coimbrai with projections for the current scenario and under different management alternatives. To collect data on populations of C. coimbrai, an active search was carried out on forest fragments, besides interviews with local residents, in the Atlantic Forest and transition zones with the Caatinga between the Paraguaçu River and the São Francisco River, covering 50,000 km2 throughout the State of Sergipe and northern coast of Bahia. For potential distribution modeling with the software Maxent, all occurrence records available for the species of the Personatus de Callicebus group were used. Population Viability Analyzes (PVA) were performed using the software Vortex. It was estimated that about 4,500 individuals of C. coimbrai remain, spread over 125 forest fragments summing 22,500 ha, within an extension of occurrence of approximately 30,000 km², with the western limit being an ecological barrier constituted by the transition between the Atlantic Forest and the Caatinga. The results corroborate habitat loss and fragmentation as main threats to the species, which also suffers impacts from hunting, harvesting, predation by domestic animals and overruns. PVAs indicate that only populations with 100 individuals or more have a probability of survival above 95% in 100 years, with at least 200 individuals required to maintain an average genetic diversity of at least 90% for the same period. The continuous population decline due to habitat fragmentation and other threats tends to reach practically irreversible levels, from which it becomes progressively more difficult and complex to guarantee the viability of the species' populations. Due to the situation of these populations and the high risk of extinction of the species, comprehensive and transdisciplinary strategic actions are essential and urgent to reverse this situation and ensure the survival of C. coimbrai, such as the protection of the main areas of occurrence, promotion of the connectivity of habitats and, eventually, intensive metapopulation management.